Mongolian Tolerance and Intolerance Toward Different Cultures: An Exploration Based on Analyses of Cross-National Survey Data - Minato, Kunio (Acta Mongolica, 2014)
The rise and rampancy of ultranationalists has been repeatedly reported in Mongolia in recent years, but whether views and actions characterized by ultranationalism are prevalent remains to be determined. Some insist that ultranationalists are gaining in popularity, and others deny that such groups represent the majority of the Mongolian people. However, the grounds of these arguments are unclear. To elucidate this question on an empirical basis, I examined how tolerant and intolerant Mongolians are to people of different cultural backgrounds based on statistical analyses of cross-national survey data. A comparison among post-socialist countries reveals that although people with intolerant attitudes toward those from different cultures remain in the minority in Mongolia, the percentage of such people is relatively high compared with other post-socialist countries; in particular, a negative attitude toward foreign workers and immigrants is clearly observed. The result demonstrates the potential risk of the spread of exclusivism in Mongolia.